Psychological Literacy and Undergraduate Psychology Education: An International Provocation - Cranney, Jacquelyn; Dunn, Dana S.; Hulme, Julie A.; Nolan, Susan A.; Morris, Sue; Norris, Kimberley (Frontiers in Education, 2022)
For over 50 years, psychology leaders have called for fundamental changes in how we undertake research, education, and community interaction. This paper provocatively argues the case for “why now, and how.” The COVID-19 pandemic demonstrated that psychology must contribute more to the wellbeing of local and global communities. We propose that a primary mechanism for doing so is by reinventing the undergraduate psychology program. This paper provides a stimulus to initiate international discussion of interconnected graduate capabilities, which we propose to be: Knowledge, Research Methods, Application of Knowledge to Personal, Professional and Community (Local, National, Global) Domains, Values and Ethics, Critical Thinking, Communication, and Cultural Responsiveness. Focusing on core aspects of psychology (Knowledge, Research Methods, Application) and more generic but evidence-informed capabilities is a unique formulation and should well serve graduates, employers, society, and the psychology discipline and profession in the uncertain “post-pandemic” era. We also propose psychological literacy as a promising unifying approach for psychology. Finally, we provide a “road-map” for curriculum renewal at international, national, and institutional levels, involving a consensus-seeking process (an extensive scholarly overview of the proposed capabilities is provided).